2008
DOI: 10.1186/1476-072x-7-4
|View full text |Cite
|
Sign up to set email alerts
|

Dioxin emissions from a municipal solid waste incinerator and risk of invasive breast cancer: a population-based case-control study with GIS-derived exposure

Abstract: BackgroundTo date, few epidemiologic studies have examined the relationship between environmental PCDD/F exposure and breast cancer in human populations. Dioxin emissions from municipal solid waste incinerators (MSWIs) are one of the major sources of environmental dioxins and are therefore an exposure source of public concern. The purpose of this study was to examine the association between dioxins emitted from a polluting MSWI and invasive breast cancer risk among women residing in the area under direct influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 21 publications
1
37
0
2
Order By: Relevance
“…This switch-like function is compatible with the existing model of the role of the AHR in the cell cycle while extending the model to provide a mechanism by which the receptor can also facilitate cell cycle progression. Within mammary epithelial cells, the integrated model can explain both the lack of mammary development in the AHR knockout mice, in which facilitation of cell cycle progression by the receptor is absent (Hushka et al, 1998), as well as the epidemiological and rodent data demonstrating the inhibition of mammary tumorigenesis by exogenous AHR ligands (Bertazzi et al, 1997;National Toxicology Program, 2006;Viel et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This switch-like function is compatible with the existing model of the role of the AHR in the cell cycle while extending the model to provide a mechanism by which the receptor can also facilitate cell cycle progression. Within mammary epithelial cells, the integrated model can explain both the lack of mammary development in the AHR knockout mice, in which facilitation of cell cycle progression by the receptor is absent (Hushka et al, 1998), as well as the epidemiological and rodent data demonstrating the inhibition of mammary tumorigenesis by exogenous AHR ligands (Bertazzi et al, 1997;National Toxicology Program, 2006;Viel et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The result showed increasing dioxin intake levels associated with declining breast cancer risk in post-menopausal women with ER-negative/PR-negative tumors [59]. In contrast, epidemiological case-control studies found no apparent association between dioxin exposure and breast cancer [80][81].…”
Section: Dioxinsmentioning
confidence: 63%
“…A study from Russia reported higher risk of breast cancer among women living in the area of a chemical plant which contaminated the surrounding environment with dioxins (62). However, Viel et al (63) did not fi nd an association between breast cancer risk in younger women and exposure to dioxins emitted from a local incinerator. Moreover, the study showed a decreased risk in older women who lived in the area, which was highly polluted with dioxins.…”
Section: Health Effectsmentioning
confidence: 97%
“…Some epidemiological studies investigated the relationship between dioxin exposure and breast cancer risk (61)(62)(63). A study which included women from Seveso found a signifi cantly increased risk of breast cancer associated with increased TCDD in serum (61).…”
Section: Health Effectsmentioning
confidence: 99%